TINGKAT KEPUASAN PETERNAK AYAM BROILER TERHADAP POLA KEMITRAAN PT. CIOMAS ADISATWA KABUPATEN JEMBER - Nadintha Rahmaaisya; Illia Seldon Magfiroh; Intan Kartika Setyawati; Ratih Apri Utami; Yuli Hariyati (CV Widina Media Utama, 2026)
In expanding its business, PT Ciomas Adisatwa Jember endeavors to evaluate its partnerships, particularly those with broiler farmers in Jember Regency. The company aims to determine whether its partner farmers are satisfied with the collaboration. This study aims to analyze the nucleus-plasma partnership model of PT Ciomas Adisatwa Jember Regency, assess farmer satisfaction with the partnership, and formulate partnership development strategies for the company. The partnership model was analyzed descriptively, farmer satisfaction was evaluated using the Customer Satisfaction Index (CSI), and the partnership strategy was analyzed through Importance-Performance Analysis (IPA). The results of the study indicate the following: First, the implementation of the nucleus-plasma partnership model at PT Ciomas Adisatwa Jember is established with the company acting as the nucleus and the farmers as the plasma. Second, the Customer Satisfaction Index (CSI) score of the partner farmers is 78.86%, falling into the